Why Architects See Things Differently An Architectural Approach On Teaching Space Perception - Julean, Dana (European Scientific Journal, ESJ, 2016)
Space is all around us, we experience it as shaped into buildings, rooms, tiny enclosures, as well as shaped into public spaces, squares, streets, and as natural landscapes. However, when we look at it, interact with it, walk through it, we all experience it differently. Psychology teaches us that the perceptual process is a very complex mechanism, which is essentially made up of two aspects: “one of which is essentially figurative, related to the percepts or images of successive states or momentary configurations of the world by direct and immediate contact, and a second which is essentially operative, related to the operations which intervene between successive states and by which the subject transforms parts of the world into reconstructable patterns or schemas.” (Hart & Moore, 1973, p. 249). Thus, when looking at space, although we all “see” the same thing, we operate and understand things differently mainly because of our different social, cultural, religious, and geographical backgrounds (Downs & Stea, 1973). Therefore, the present study would like to focus precisely on this aspect, namely why do architects perceive space differently than the ordinary passerby?